Private security sector employees; labour practices and challenges faced in securing decent work: case study of professional - Chimbari, Kudakwashe (Midlands State University, 2018)
The main thrust of this research was to investigate the labour practices and challenges faced in securing decent work for private security sector employees. The research was conceptually guided by the Human Development concept. Twenty-eight participants were drawn from various categories which included HR personnel, management, workers’ committee and security guards. In selecting these participants from the categories of HR personnel, management and workers’ committee, the researcher made use of purposive non-probability sampling while convenience sampling was used to select security guards. Semi-structured interviews were used to solicit information from the HR officer, management, and workers’ committee members. Semi-structured questionnaires were administered to gather data from security guards. The major findings of the research revealed that security guards are working under deplorable conditions and these include but not limited to very long working hours, non-payment of wages, and non-provision of health working environment. However, a handful of good labour practices that have the potential of securing decent work if fully utilized were also observed, these include gender mainstreaming, and workplace collective bargaining. The research findings also unearthed challenges faced in securing decent work for private security employee. The researcher concluded that private security employees are working under indecent working conditions which require serious and urgent attention from all stakeholders if decent work is to be achieved to this class of employees. From the foregoing, the researcher proffered recommendations that can be used to secure decent work for the security guards.